Top management team diversity: Organisations becoming the architects of their own downfall. A case study of the effects of top management team characteristics on organisational decision-making. - Mcloughlin, Joseph (2018)
This study examines the role that demographic characteristics play in top management team decision-making and whether a lack of diversity in the characteristics of top management team members leads to poor decision-making. The literature demonstrates that demographic characteristics have an effect on an individual’s values and perspectives, which can influence what strategies they decide upon. Although some studies have highlighted the negative effects of heterogenous top management teams, the literature suggests that diverse top management teams perform better and choose optimal strategies for their organisations due to the input of varied perspectives and values into decisions. A case study approach was used to investigate Barings Bank, Enron and Carillion, who all had collapsed due to accounting malpractices and poor decision-making. It was found that in the cases of Barings Bank and Enron, little or no diversity existed within their top management teams during the years leading up to their collapse. For Carillion, some diversity existed within only a few characteristics, with other characteristics remaining predominantly homogenous. These results suggest that in the cases analysed, a lack of overall diversity amongst the top management teams was related to their demise. This supports the need to encourage diversity within organisations to improve their chances of survival, with this thesis offering a number of recommendations for organisations in line with this.